PENEGAKAN HUKUM TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN TENTARA NASIONAL INDONESIA DIKAITKAN DENGAN MEDIASI PENAL DALAM PERADILAN MILITER (UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 31 TAHUN 1997) - Rivaldi Fajarhari; Abdul Abdul Muis BJ (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2021)
ABSTRACT The prosecutor can return the case to the POM as investigator for penal mediation and POM as mediator. Settlement of criminal cases that occur can be resolved by two methods, namely penal and non-penal. One of the non-penal settlement is Penal Mediation. Penal mediation itself is born from the culture that exists in society so that the contents of the values are in accordance with the characteristics of the Indonesian Nation. However, the application of penal mediation does not yet have a strong juridical foundation. The research method used is descriptive analytical approach method and normative juridical research specifications. Meanwhile, the data analysis used qualitative juridical methods. Law Enforcement of the Offenses of Persecution by the Indonesian National Armed Forces Related to Penal Mediation in Military Courts (Law of the Republic of Indonesia Number 31 of 1997) means that in the military there is no penal mediation. The auditor has the prerogative rights. Obstacles in Law Enforcement Crime of Persecution by TNI Associated with Penal Mediation in Military Courts (Law of the Republic of Indonesia Number 31 of 1997) are internal factors, namely: prosecutors are hesitant to apply penal mediation, external factors, namely: the victim is not willing to undergo penal mediation. Keywords: Law Enforcement, Persecution Crime, Military Penal Mediation